Analisis Indeks Kekeringan DAS Siak Menggunakan Metode Keetch Byram Drought Index (KBDI) - Ikhsan Aulia Rudy; Manyuk Fauzi; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Riau Province is one of the drought stricken provinces in Indonesia. Droughts can adverse impacts suchas land fires. Based on data from the Ministry of Environment and Forestry in 2013, Riau Province hasthe most hotspot in Indonesia with the 5,128 hotspot. The meteorological drought index can be used asinformation for policymaking as an effort to prevent land fires. This research was conducted in Siakwatershed of Riau Province using KBDI method and length of data used last 10 years. The analysis wasused rain data recorded from four rain stations in the Siak watershed. The result of the analysis showsthat the highest drought index value of KBDI method occurred in Petapahan Baru Station, April 2015which was 1965,919 with the classification of Extreme. Based on the correlation of drought index of Siakwatershed with hotspot data, the highest value of correlation is 0,859 in 2009 with a very strong category.Keywords: Hotspot, meteorological drought index, KBDI.